Donald Horne interviewed by Hazel de Berg in the Hazel de Berg collection (1973) - Horne, Donald, 1921-2005.; De Berg, Hazel, 1913-1984. (1973)
Horne speaks of the reasons for writing his first book "The permit" ; the genesis of his book "The lucky country" ; his method of writing and researching "The lucky country" ; Horne speaks of his literary production, especially "The education of young Donald" ; he gives autobiographical details of his childhood and work experiences.
Digital master available
Transcript available (12 p.)
Keywords: Horne, Donald, -- 1921-2005 -- Interviews; Editors -- Australia -- Interviews; Novelists, Australian -- Interviews